Neural Mechanisms of Hearing Recovery for Cochlear-Implanted Patients: An Electroencephalogram Follow-Up Study - Wang, Songjian; Lin, Meng; Sun, Liwei; Chen, Xueqing; Fu, Xinxing; Yan, LiLi; Li, Chunlin; Zhang, Xu (Frontiers in Neuroscience, 2021)
Abstract Patients with severe-profound hearing loss could be benefited from cochlear implantation (CI). However, the neural mechanism of such benefit is still unclear. Therefore, we analyzed the electroencephalogram (EEG) and behavioral indicators of auditory function remodeling in patients with CI. Both indicators were sampled at multiple time points after implantation (1, 90 and 180 days). Methods: First, the speech perception ability was evaluated with the recording of a list of Chinese words and sentences in 15 healthy controls (HC group) and 10 patients with CI (CI group). EEG data were collected using an oddball paradigm. Then, the characteristics of event-related potentials (ERPs) and mismatch negative (MMN)were compared between CI group and HC group. In addition, we analyzed the phase lag indices (PLI) in CI group and HC group, and calculated the difference in functional connectivity between the two groups at different stages after implantation. Results: The behavioral indicator, speech recognition ability, in CI patients improved as the implantation time increased. The MMN analysis showed that CI patients could recognize the difference between standard and deviation stimuli just like the healthy controls 90 days after cochlear implantation. Comparing the latencies of N1/P2/MMN between CI group and HC group, we found that the latency of N1/P2 in CI patients was longer, while the latency of MMN in CI users was shorter. In addition, PLI-based whole-brain functional connectivity（PLI-FC）showed that the difference between CI group and HC group mainly exists in electrode pairs between bilateral auditory area and frontal area. Furthermore, all those differences gradually decreased with the increase in implantation time. Conclusions: The N1 amplitude, N1/P2/MMN latency and PLI-FC in the alpha band may reflect the process of auditory function remodeling and could be an objective index for the assessment of speech perception ability and the effect of cochlear implantation.